Response of Super Dosing of Phytase on Growth Performance and Bone Characteristics in Broilers Fed with Low Phosphorus and Calcium Diets - Ali, Sayda Awad; Elangovan, A. V.; Shet, D.; Awachat, V. B.; Ghosh, J.; Pal, D. T.; Gowda, N.K. S. (Indian Journal of Animal Nutrition, 2017)
A feeding trial was conducted to assess the effect of super dosing of phytase in either normal or low phosphorus or low calcium corn-soy based diets of broiler chicken. A total of 112 healthy, day-old, Cobb chicks were distributed randomly to 4 treatments with 4 replicates each having 7 chicks. In the first two groups, normal recommended P diet (0.45% available P during starter and 0.40% during finisher phase) was fed without phytase supplementation (control) or supplemented with phytase (@ 2500 FTU; phytase unit/kg diet). The third group was supplemented with phytase (@ 2500 FTU/kg diet) to a low P (0.31% available P during starter and 0.15% during finisher phase) diet with normal Ca (1% Ca in diet). In the fourth group, it was similar to third diet but with lower (0.8%) level of Ca. The inorganic P was not added to third and fourth groups during finisher phase. The body weight gain and feed intake of chicks were similar during starter, finisher and overall phase. The feed conversion ratio was lower in the third group during finisher phase as compared to other 3 groups, however, it was similar when compared during overall phase. The bone morphology and mineralization was not affected either by normal or lower P levels in diet supplemented with super dosing of phytase. The results indicated that super dosing of phytase on low P and Ca diets were beneficial than the normal standard dose of phytase in diet of broiler chicken.